The first mitochondrial genome of a South America parthenogenetic lizard (Squamata: Gymnophthalmidae) - Tuliana O. Brunes; Mariana L. Lyra; José A. Maldonado; Katia C. M. Pellegrino; Miguel Trefaut Rodrigues; Matthew K. Fujita (Mitochondrial DNA. Part B. Resources, 2021)
The mitogenome of the South American parthenogenetic lizard Loxopholis percarinatum Müller, 1923 (Squamata: Gymnophthalmidae), a uni-bisexual species complex, was recovered for three individuals from Rio Negro region, Amazonas, Brazil. The content and order of genes are typical for vertebrate mitochondrial genomes, and we recovered 13 protein-coding genes, 22 tRNA, and two rRNA (12S and 16S), in addition to partial fragments of the Control Region. A maximum likelihood phylogenetic analysis with mitogenomes of selected lizard families recovered L. percarinatum with Iphisa elegans Gray, 1851, the only other Gymnophthalmidae species available in GenBank.